Association Between Storage Interval and Contamination of Reprocessed Flexible Endoscopes in a Pediatric Gastrointestinal Procedural Unit. (7th November 2016) - Scanlon, Patricia; Flaherty, Kathleen; Reilly, Erik A.; Barth, Ellen G.; Potter-Bynoe, Gail; Cardini, Jeff; Riley, Ann Marie; McAdam, Alexander J.; Sandora, Thomas J.
Abstract : OBJECTIVE: The maximum safe storage interval after endoscope reprocessing remains unknown. We assessed the association between storage interval and endoscope contamination to evaluate the need for scope reprocessing prior to use. METHODS: We conducted a study in 2 phases. In phase 1, we cultured 9 gastrointestinal (GI) endoscopes that had been stored for at least 7 days since reprocessing. Each scope was cultured in 3 places: external surfaces of hand piece, insertion tube, and internal channels. In phase 2, after reprocessing these scopes, we hung and cultured them prospectively in a similar fashion at 1-, 2-, 4-, 6-, and 8-week intervals without patient use. We defined clinically relevant contamination as >100 colony-forming units per milliliter (CFU/mL). RESULTS: In phase 1, median hang time was 69 days (range, 8–555 days). Considering the 27 total cultures, 3 of 27 GI endoscopes (11.1%) had positive cultures, all with nonpathogenic skin flora at ≤100 CFU/mL. Median hang time was not statistically different between scopes with positive and negative cultures ( P =.82). In phase 2, 7 of 131 prospective cultures (5.3%) from 6 of 9 GI endoscopes at varying storage intervals were positive, all at ≤100 CFU/mL. At 56 days after reprocessing (the longest storage interval studied), 1 of 24 cultures (4.2%) was positive (100 CFU/mL of Bacillus species from external biopsy/suction ports). CONCLUSIONS: No endoscopes demonstrated clinically relevant contamination at hang times ranging from 7 to 555 days, and most scopes remained uncontaminated up to 56 days after reprocessing. Our data suggest that properly cleaned and disinfected GI endoscopes could be stored safely for longer intervals than currently recommended. Infect. Control Hosp. Epidemiol. 2017;38:131–135